Effect of monoterpene ester from Blumea axillaris (Lam.) DC and its acetyl derivative against plant pathogenic fungi and their in silico molecular docking. Issue 24 (17th December 2021) - Sivanandhan, Subramaniyan; Pathalam, Ganesan; Antony, Stalin; Michael, Gabriel Paulraj; Balakrishna, Kedike; Boovaragamurthy, Ahilan; Shirota, Osamu; Alwahibi, Mona S; El-Shikh, Mohamed Soliman; Ignacimuthu, Savarimuthu
Abstract: The present study was aimed to isolate active constituents from Blumea axillaris (Lam.) DC (Asteraceae) against phytopathogenic fungi. Bioactivity guided fractionation of the successive n -hexane, chloroform and methanol extract led to the isolation of the monoterpene ester (4  R, 5 S )-4-hydroxy-7-tigloyloxycarvotanacetone (1). The compound 1 was converted into acetyl derivative (2). The acetyl derivative (2) and the parent compound 1 were tested again phytopathogenic fungi by using mycelial inhibition and minimal inhibitory concentration values were found out by the broth microdilution method. The acetyl derivative (2) showed the highest antifungal activity against Rhizoctonia solani and Aspergillus niger . Based upon in vitro results, compound 1 was tested against Fusarium oxyporum (wilting disease) and compound 2 was tested against R. solani (leaf blight disease) in vivo using the foliar spray method. Both compounds had no phytotoxicity and also in silico docking study showed that both compounds were binding similarly as commercial fungicide carbendazim. Abstract : UF0001